Galbraith Award 133 Bilateral Failure of Cerebral Autoregulation is Related to Unfavorable Outcome After Subarachnoid Hemorrhage. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Budohoski, Karol P.; Kirkpatrick, Peter J.; Smielewski, Peter; Reinhard, Matthias; Varsos, Georgios V.; Kasprowicz, Magdalena; Zabek, Miroslaw; Pickard, John Douglas; Czosnyka, Marek
Abstract: INTRODUCTION: The extent of hemodynamic disturbances following subarachnoid hemorrhage (SAH) varies. We aim to determine the prognostic implications of unilateral and bilateral autoregulatory failure on delayed cerebral ischemia (DCI) and outcome. METHODS: Ninety-eight patients with aneurysmal SAH were recruited. Autoregulation was assessed using systolic flow index Sxa. Interhemispheric difference was calculated. Patients were dichotomized by presence of DCI and 3-month outcome using the mRS. RESULTS: Higher flow velocity (FV) and worse autoregulation ( P < .0000001; 95% confidence interval [CI]: 10.7-21.3; and P = .00001; 95% CI: 0.03-0.07 for difference in FV and Sxa, respectively) were found in the ipsilateral hemisphere. The DCI group had a higher interhemispheric difference of autoregulation than the non-DCI group ( P = .0004; 95% CI: 0.03-0.09). 16/18 patients with unfavorable outcome had poor autoregulation with low interhemispheric differences vs 17/72 patients with favorable outcome ( P = .0013 χ 2 ). Unilateral autoregulatory failure was seen on a median day 3, bilateral on day 4, and vasospasm was detected on day 6. Unilateral autoregulation failure was seen in patients who developed DCI (worse ipsilateral to the ischemic hemisphere). CONCLUSION: Bilateral autoregulation failure was seen more frequently in patients with unfavorable outcome. Analysis of the temporal profile showed unilateral dysautoregulation as the primary predisposing to DCI, and in selected cases leads to bilateral failure and unfavorable outcomes.